Substantial Increase in Heavy Precipitation Events Preceded by Moist Heatwaves Over China During 1961–2019 - Li, Chenxi; Min, Ruiying; Gu, Xihui; Gulakhmadov, Aminjon; Luo, Sijia; Liu, Ruihan; Slater, Louise J.; Xie, Fenghua; Kong, Dongdong; Liu, Jianyu; Li, Yanan (Frontiers in Environmental Science, 2022)
Both moist heatwaves (HWs) and heavy precipitation events (HP) have increased in both frequency and magnitude over China in recent decades. However, the relationship between HW and HP, and changes in the lagged coincidence of events (i.e. the occurrence of a HP event several days after a HW event, noted HWHP) remain unknown. We show here that HWHP events account for nearly one-third of HP events over China in summer, with high values in North China, Northeast China, and the East arid zone. HWHP events assessed using the heat index and the wet-bulb temperature methods increased by 45.25% and 23.97% from 1961 to 2019, respectively. These concurrent HWHP events tend to be spatially clustered, and the areas affected simultaneously have grown significantly. The increase in HW is the major driver of these changes in HWHP events, except in the Western arid zone and North China. Our findings provide an understanding of the spatio-temporal changes in HWHP events over China and their implications for disaster mitigation.